Age‐related changes in reticulospinal contributions to anticipatory postural adjustments between back extensors and abdominal muscles - Shin‐Yi Chiou; Catherine Unwin; Alice Lilley (Experimental Physiology, 2024)
Abstract Anticipatory postural adjustments (APAs) give feedforward postural control of the trunk, but they are delayed with ageing, affecting balance and mobility in older individuals. The reticulospinal tract contributes to postural control of the trunk; however, the extent to which age‐related changes affect the reticulospinal contributions to APAs of the trunk remains unknown in humans. Here, we tested the hypothesis that a startling acoustic sound, which activates the reticulospinal tract, improves delayed APAs in older individuals. Twenty‐two old (75 ± 6 years) and 20 healthy young adults (21 ± 4 years) performed a self‐initiated fast bilateral shoulder flexion or shoulder extension task in response to visual, visual and auditory (80 dB), or visual and startling (115 dB) cues. Electromyography (EMG) was recorded from bilateral anterior deltoid (AD) and erector spinae (ES) during shoulder flexion and from bilateral posterior deltoid (PD) and rectus abdominis (RA) during shoulder extension. EMG onset of all muscles shortened during the startling cue in both age groups, suggesting a non‐specific modulation of the reticulospinal tract on prime movers (AD or PD) and non‐prime movers (ES or RA). Interestingly, APAs of the ES were accelerated in older participants to a similar degree as in younger participants during the startling cue. Conversely, APAs of the RA were not influenced by the startling cue in older participants. Our results suggest differential effects of ageing on functional contributions of the reticulospinal tract to APAs between back extensors and abdominal muscles.